1998
DOI: 10.2307/1132138
|View full text |Cite
|
Sign up to set email alerts
|

Parenting and Preschooler Attachment among Low-Income Urban African American Families

Abstract: This study examined the parental correlates of child attachment in a preschool-aged, economically disadvantaged, urban, African American sample. Sixty-nine 4- to 5-year-olds and their primary caregivers participated in the Strange Situation assessment procedure. Based on Cassidy and Marvin's classification system for preschoolers, 61% of the children were classified as securely attached, with girls being significantly more likely to be securely attached than boys (74% versus 45%). The majority of the insecure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 57 publications
6
55
0
Order By: Relevance
“…Despite the perception that Black mothers are more loving with their sons than with their daughters, in a study of attachment patterns among urban, low-income, Black preschool-age children, Barnett et al (1998) found that girls were more likely to be securely attached than boys. Puzzled by this result, the authors called for research on low-income Black mothers' differential expectations and goals for raising daughters as compared to sons.…”
Section: Gender Socialization In Inner-city Black Familiesmentioning
confidence: 91%
See 1 more Smart Citation
“…Despite the perception that Black mothers are more loving with their sons than with their daughters, in a study of attachment patterns among urban, low-income, Black preschool-age children, Barnett et al (1998) found that girls were more likely to be securely attached than boys. Puzzled by this result, the authors called for research on low-income Black mothers' differential expectations and goals for raising daughters as compared to sons.…”
Section: Gender Socialization In Inner-city Black Familiesmentioning
confidence: 91%
“…Some research shows few differences between parental behaviors directed toward boys versus girls, especially when children are pre-pubertal. Barnett et al (1998), for example, found that Black mothers of 4-and 5-year-olds were similar in terms of warmth and level of control whether their children were boys or girls. Similarly, Ispa et al (2004) andMcGroder (2000) reported no genderof-child differences in the degree of mothers' warmth or negativity directed toward toddlers or preschoolers.…”
Section: Gender Socialization In Inner-city Black Familiesmentioning
confidence: 99%
“…We hypothesized, therefore, that security would be associated with greater child responsiveness, self-assertiveness, and committed compliance (high-approach behaviors) for children high on anger proneness, and we explored whether security was related to more help-seeking behavior (low-approach behavior) for children low on anger proneness. Importantly, child-mother attachment security has been associated with greater maternal sensitivity (e.g., Barnett et al, 1998;NICHD ECCRN, 2001), and young children tend to be responsive toward, and seek support from, mothers who are more sensitive (e.g., Schieche & Spangler, 2005). Thus, we included observed maternal sensitivity as a covariate in the main analyses to control for the possibility that associations between child-mother attachment security and child behavior were accounted for by more sensitive mothering.…”
Section: The Current Studymentioning
confidence: 99%
“…Several studies show that parents, mainly mothers, of children classifi ed as (more) secure in preschool or early school years show higher levels of sensitivity, warmth and acceptance, open communication, emotional openness, role balance, and mutual responsiveness and enjoyment of the child, and less controlling behaviors and negativity, than parents of children classifi ed as insecure (Barnett, Kidwell, & Leung, 1998 ;Booth, Rose -Krasnor, McKinnon, & Rubin, 1994 ;Diener, Nievar, & Wright, 2003 ;Moss, Bureau, Cyr, Mongeau, & St. -Laurent, 2004 ;Moss, Cyr, & Dubois -Comtois, 2004 ;NICHD ECCRN, 2001 ;Stevenson -Hinde & Shouldice, 1995 ). Similarly, securely attached children in later middle childhood have parents who are more accepting (Kerns, Klepac, & Cole, 1996 ;Kerns, Tomich, Aspelmeier, & Contreras, 2000 ;Yunger, Corby, & Perry, 2005 ), and are more aware of their children ' s activities and whereabouts in the sixth grade, but not third grade (Kerns et al, 2001 ).…”
Section: What Factors Promote Individual Differences In Attachment?mentioning
confidence: 99%